Mathematically Gifted Students’ Experience With Their Teachers’ Mathematical Competence and Boredom in School: A Qualitative Interview Study - Smedsrud, Jørgen Hammer; Nordahl-Hansen, Anders; Idsøe, Ella (Frontiers in Psychology, 2022)
Competent mathematics teachers who have knowledge of gifted students’ needs can challenge them in math and prevent boredom and possible underachievement. This retrospective study explores how Norwegian gifted students perceive their earlier teachers’ mathematical competency, as well as their reflections about boredom in school. The data were collected through qualitative semistructured interviews with 11 mathematically gifted students who participated in accelerated classes throughout school. The informants ranged in age from 16 to 19 years and were asked about how they experienced their math classes, teachers, and social aspects. The results indicate that students view their teachers as having less mathematical knowledge in earlier school than in later years and that teachers’ mathematical knowledge might affect whether they are able to challenge and identify students who are gifted in mathematics.